Phorbol ester induces photoreceptor-specific degeneration in a Drosophila mutant. - Minke, B (1990)
In the retinal degeneration B (rdgB) mutant of Drosophila, the major class of photoreceptors degenerate when the fly is raised in the light for several days; raising the fly in the dark largely prevents the degeneration. Thus, the rdgB is a conditional mutant that requires the operation of some stages of the phototransduction cascade to express its characteristic phenotype. We report here experiments that examine the ability of chemical agents to mimic light by causing photoreceptor-specific degeneration in the dark. Application of a specific activator of protein kinase C, phorbol ester, to eyes of rdgB flies led to a degeneration of the photoreceptors that was indistinguishable from that caused by light: both light and phorbol ester-induced degeneration were characterized by (i) selective degeneration of one class of photoreceptors; (ii) a unique pattern of degeneration; and (iii) the appearance of light-induced regenerative spikes at early stages of degeneration. Application of phorbol ester to the eyes of wild-type flies had no effect. We suggest that light or phorbol ester activates a protein kinase C and results in a sustained or excessive phosphorylation of proteins in the rdgB mutant, leading to photoreceptor degeneration. Furthermore, the results are consistent with identification of the rdgB gene product as a phosphoprotein phosphatase that is nonfunctional or absent in the mutant.